Assessment of Climatic Water Balance and Quality of Shallow Aquifer Groundwater Around Al-Garraf River (Southern Iraq) - A. Al-Dabbas, Moutaz; Al-Shamma, Ayser; Ghful Al-Mitawki, Kareem (Al-Qadisiyah Journal of Pure Science, 2018)
Al- Gharraf River is one of the most important and longest-running rivers in southern Iraq, where water is moving from Kut towards Dhi Qar governorate. In this study, the climatic water balance of the studied area was determined by using the climatic parameters of the Al-Hay meteorological station. The geology and the formal shallow unconfined aquifer of the area is quaternary sediments which are overlain lower Miocene carbonates. The recharge of groundwater depends mainly on rainfall and the irrigation water. The analysis of climatic parameters, gave the idea that the average monthly temperature is ranging from 17.1- 45.4 CÂ°, rainfall (0-31.7 mm), evaporation (526.4 mm in July) and (49.1 mm in January). The water surplus is about 55.327 while the water deficit is 1678.83 mm. The analysis of major ions, gave the idea that the studied wells recorded high TDS, which ranges between 1116 mg/l to2300 mg/l. Durov and Piper diagrams were used to present the data. Most of the groundwater samples are plotted in fields 5 which indicates no domination of cation or anion, this mean that process was mixed the recharge groundwater with surface water (rain and irrigation). All groundwater samples are brackish water.